Theoretical Modeling of Defects, Dopants, and Diffusion in the Mineral Ilmenite - Kuganathan, N.; Srikaran, R.; Fossati, P.C.M.; Chroneos, A. (My University, 2019)
Abstract: The iron titanium oxide ilmenite (FeTiO3) is a technologically and economically important mineral in the industrial preparation of titanium-based pigments and spintronic devices. In this study, atomistic simulation techniques based on classical pair potentials are used to examine the energetics of the intrinsic and extrinsic defects and diffusion of Fe2+ ions in FeTiO3. It is calculated that the cation anti-site (Fe-Ti) cluster is the most dominant defect, suggesting that a small amount of cations exchange their positions, forming a disordered structure. The formation of Fe Frenkel is highly endoergic and calculated to be the second most stable defect process. The Fe2+ ions migrate in the ab plane with the activation energy of 0.52 eV, inferring fast ion diffusion. Mn2+ and Ge4+ ions are found to be the prominent isovalent dopants at the Fe and Ti site, respectively. The formation of additional Fe2+ ions and O vacancies was considered by substituting trivalent dopants (Al3+, Mn3+, Ga3+, Sc3+, In3+, Yb3+, Y3+, Ga3+, and La3+) at the Ti site. Though Ga3+ is found to be the candidate dopant, its solution enthalpy is >3 eV, suggesting that the formation is not significant at operating temperatures.
Keywords: Ilmenite; Defects; Dopants; Diffusion; Activation energy